2 Ballinger’s Annotated Codes and Statutes of Washington, Showing All Statutes in Force, Including the Session Laws of 1897, at 1956–57, § 7084 (1897) - (:unkn) unknown (General Publisher, 1897)
Prohibited the carrying of a concealed revolver, pistol, or other fire-arms, or any knife, (other than an ordinary pocket knife), or any dirk or dagger, sling-shot, or metal knuckles, or any instrument by the use of which injury could be inflicted upon the person or property of any other person. Punishable by fine of $25-100 and/or imprisonment for 30 days.
--
Keywords: CARRY - CONCEALED